Endoscopic mucosal autograft for treating esophageal caustic strictures: preliminary human experience - He, Kexin; Zhao, Lili; Bu, Shoushan; Liu, Li; Wang, Xiang; Wang, Min; Fan, Zhining (Endoscopy, 2018)
Background Esophageal caustic stricture is a stubborn disease and postoperative restenosis limits the clinical efficacy of endoscopic dilation. Autologous mucosal grafts have been successfully applied in the treatment of urethral stricture and in the prevention of stricture after extensive mucosal resection. We aimed to use mucosal autografting performed endoscopically to treat refractory esophageal stricture.Methods Three patients with intractable corrosive esophageal stricture were treated endoscopically by combining dilation with autologous mucosal transplantation. Results All procedures were successful with no severe complications. Mucosal regeneration was shown at the transplanted segments. One patient was able to maintain a normal diet with complete remission after 1 year of follow-up. Intraluminal stenosis and dysphagia were significantly improved in another two patients. Conclusions Mucosal autografting can achieve esophageal re-epithelialization, inhibit undesired fibrosis, prevent restenosis, and promote functional regeneration.